Increased market transparency in Germany's gasoline market: What about rockets and feathers? - Manuel Frondel; Marco Horvath; Colin Vance; Alexander Kihm (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
Drawing on panel data on daily fuel prices covering over 5,000 filling stations in Germany, this paper documents a change in the stations' price setting behavior following the introduction of a legally mandated online price portal in 2013. Prior to the portal, positive asymmetry is found on the basis of error correction models, with prices following the "rockets and feathers" pattern that is typically found for fuels. In the aftermath of the portal, by contrast, negative asymmetry is observed: fuel price decreases in response to refinery price decreases are stronger than fuel price increases due to refinery price increases. – – Dieses Paper analysiert einen Paneldatensatz täglicher Kraftstoffpreise von über 5000 Tankstellen in Deutschland und dokumentiert eine Änderung des Preissetzungsverhaltens von Tankstellen in Folge einer gesetzlich angeordneten Einführung eines Online-Preisportals im Jahr 2013. Vor Einführung des Portals wird auf der Grundlage eines Error-Correction-Models eine positive Preisasymmetrie gefunden und die Preise folgen dem "Rockets and Feathers"-Muster, welches typisch für Kraftstoffpreise ist. Nach Einführung des Portals hingegen ist eine negative Asymmetrie zu beobachten: Die Kraftstoffpreissenkungen als Reaktion auf die Preissenkungen bei den Raffineriepreisen sind stärker als die Kraftstoffpreissteigerungen aufgrund von Preiserhöhungen bei Raffinerien.
Keywords: D12; Q41; 330; retail markets; competition; error correction model